Mathematical modelling of extracellular matrix dynamics using discrete cells: Fiber orientation and tissue regeneration - Dallon, J; Sherratt, J; Maini, P (1999)
Matrix orientation plays a crucial role in determining the severity of scar tissue after dermal wounding. We present a model framework which allows us to examine the interaction of many of the factors involved in orientation and alignment. Within this framework, cells are considered as discrete objects, while the matrix is modelled as a continuum. Using numerical simulations, we investigate the effect on alignment of changing cell properties and of varying cell interactions with collagen and fibrin.